1999
DOI: 10.1088/0953-8984/11/2/006
|View full text |Cite
|
Sign up to set email alerts
|

Tunnelling and point contact spectroscopy of the density of states in quasicrystalline alloys

Abstract: Point contact and tunnelling experiments performed at low temperatures were used to study the electronic behaviour of the icosahedral quasicrystalline alloys AlPdRe, AlCuFe, and AlPdMn. With samples of high quality we observed at low temperatures a zero-bias anomaly that we related to the decrease of the electronic density of states (DOS) due to the electron-electron interaction. This interaction tends to diminish the DOS at the Fermi level and can be seen as the energy pseudogap of the alloy. Our experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 54 publications
(87 reference statements)
11
78
0
Order By: Relevance
“…[17][18][19] At the time being, the very existence of such peaks remains controversial. [20][21][22] In any event, in order to make a meaningful comparison between experimental measurements and numerically calculated electronic structures, one should take into account possible phason, finite lifetime and temperature broadening effects. In so doing, it is observed that most finer details in the DOS are significantly smeared out and only the most conspicuous peaks remain in the vicinity of the Fermi level at room temperature.…”
mentioning
confidence: 99%
“…[17][18][19] At the time being, the very existence of such peaks remains controversial. [20][21][22] In any event, in order to make a meaningful comparison between experimental measurements and numerically calculated electronic structures, one should take into account possible phason, finite lifetime and temperature broadening effects. In so doing, it is observed that most finer details in the DOS are significantly smeared out and only the most conspicuous peaks remain in the vicinity of the Fermi level at room temperature.…”
mentioning
confidence: 99%
“…In a point contact junction the relevant characteristics will be related to pure Andreev reflections as Blonder et al model specifies [24]. In this work the point contacts junctions were prepared as explained by Escudero et al [18].…”
Section: Methodsmentioning
confidence: 99%
“…21 Quite interestingly the electronic structure of QCs fits in this framework in a natural way since their electronic structure is characterized by two main contributions: ͑1͒ a pronounced pseudogap at the Fermi level 2,22 and ͑2͒ several narrow spectral features in the DOS near the Fermi level. 23,24 …”
Section: Samplementioning
confidence: 99%
“…1͒ agrees well with the experimental results obtained from tunneling and point contact spectroscopy measurements, where the presence of a dip feature of small width ͑20-60 meV͒, superimposed onto a broad ͑0.5-1 eV͒ asymmetric pseudogap, has been reported. 23,[31][32][33] Thus, Eq. ͑2͒ satisfactorily describes the electronic structure of these alloys in terms of a wide Lorentzian peak ͑related to the Fermi surface-Brillouin zone interaction͒ plus a narrow Lorentzian peak ͑related to sp-d hybridization effects͒.…”
Section: ͑2͒mentioning
confidence: 99%